Hubungan Dukungan Keluarga terhadap Motivasi Ibu melakukan Deteksi Dini Kanker Serviks dengan Metode IVA - Putri, Rizka Asriyanti (Universitas Aufa Royhan, 2022)
The mother's motivation to perform early detection of cervical cancer with the IVA method can have an impact on the success of the VIA examination. One of the things that motivates a person to behave in a healthy manner and has a big impact on his health is family support. This study aims to determine the relationship between family support and the mother's motivation for early detection of cervical cancer with the IVA method. This study uses a descriptive correlational method with a cross-sectional approach. The population are mothers who have done the VIA examination. The research sample amounted to 65 people with a sampling technique. The analysis used is bivariate analysis using the chi-square test. characteristics of respondents who are majority aged 36-45 years (47.7%), married at the ideal age of 20-30 years (92.3%), have secondary education (SMA) (52.3%), do not work (73.8 % ), and have 2-4 children (78.5%). Respondents who received support from their families were 36 respondents (55.4%), and respondents who had high motivation were 33 respondents (50.8%). The results of the chi-square test between family support and motivation to carry out VIA examinations obtained a p value of (0.009) < (0.05). In conclusion, there is a relationship between family support and motivation for early detection of cervical cancer using the IVA method.